Neuroendocrine tumors of the appendix - Canbak, Tolga; Kerem Tolan, Huseyin (Annals of Medical Research, 2021)
Aim: The objective of this study was to evaluate treatment and postoperative recurrence in patients with neuroendocrine tumors of the appendix detected.Material and Methods: Patients with neuroendocrine tumors of the appendix detected between January 2015 and January 2016 were evaluated retrospectively. Patients who underwent incidental appendectomy due to different malignancies were excluded from the study. Results: A total of 402 patients who underwent appendectomy were evaluated. Five patients with neuroendocrine tumors detected, were included in the study. The mean age was 30.1 years. There were tumors in the apex, while a second tumor was found in the corpus in one patient. The mean tumor diameter was 0.6 cm. Ki-67 was under 2% in all patients. One patient underwent right hemicolectomy in the postoperative first month due to the infiltration to the periappendiceal tissue. The mean duration of hospitalization was 2 days. The mean duration of follow-up was 38 months (range 12- 54) . Ga 68 PET CT was taken in all patients after the histopathological examination. Control of the patients was performed after the first year with thorax and abdominal CT. None of the patients developed tumor. Conclusion: In general, clinical course is good and appendectomy is curative. However, right hemicolectomy is needed in patients with poor prognostic factors. Keywords: Incidental neuroendocrine tumor; appendectomy; general surgery.
Keywords: Incidental neuroendocrine tumor; appendectomy; general surgery.